The Relation of The Family Resilience with Substance on Skizofrenia Patients in The Psikiatri Unit - Nurmaela Mela Nurmaela; Suryani Suryani; Imas Rafiyah (Jurnal Keperawatan Padjadjaran, 2018)
AbstractSchizophrenic patients experience relapse after returning from the Hospital. The family is the immediate neighborhood with schizophrenic patients. Families who can not adapt to stress, then can not perform its functions properly, including the function of family care. The functioning of the family care can be seen from the level of resilience. The aim of this study was to identify the relationship between family resilience and recurrence in schizophrenic patients.This research uses correlational design with cross sectional survey. The population in this study was the family of schizophrenic patients at RSUD Arjawinangun District Cirebon. Sample determination using power analysis with alpha 0.05 and power 0.08 got sample counted 88 family. The sampling technique uses consecutive sampling. The correlation test used is Rank Spearman test. The instrument used is Family Resilience Assessment Scale which has been modified by previous researchers in Indonesia.The results of the research showed that most of the resilience of the family were tough (76.1%) and some were not tough (23.9%). The recurrence of schizophrenic patients rarely relapsed (73.9%) and a small fraction (26.1%). Rank Spearman correlation test results obtained p value = 0.001 and correlation coefficient value of 0.88, which means there is a significant relationship between family resilience with recurrence in schizophrenic patients.The conclusions of the study are resilient family resilience, allowing a rare relapse in schizophrenic patients. Arjawinangun Hospital Management Cirebon Regency in making policies to not only pay attention to the needs of patients, but also the needs of families.